A Drone as a Reflector Carrier in Laser Tracker Measurements - Jankowski Michał; Sieniło Maciej; Styk Adam (Measurement Science Review, 2022)
The paper presents the possibility of mechanizing laser tracker measurements using a drone. Performing measurements using a laser tracker requires touching the measured surface with a probe. Usually it is done manually, even if it requires, e.g., climbing a ladder. The drone was applied as a probe carrier for the laser tracker. To measure a point, the modified drone had to land near this point. Touching the measured surface with the probe was executed using a mobile arm fixed to the drone. This solution allows performing laser tracker measurements without the need of walking or climbing difficult to access surfaces. Two consecutive experiments were performed to verify if such an approach is equally accurate as the standard one (manual measurements). Additionally, the influence of airflow generated by the drones’ propellers on a laser wavelength and the accuracy of interferometric measurements were estimated. The research proves that it is possible to mechanize laser tracker measurements using a drone. Moreover, it is demonstrated that the operating drone does not influence the laser tracker accuracy.